Prevalence of xerostomia with or without overactive bladder symptoms. Issue 2 (8th October 2020) - Ito, Kayoko; Inoue, Makoto; Nishii, Hisae; Matsumoto, Tetsuro
Abstract: Overactive bladder (OAB) occurs idiopathic or secondary to a neurological cause. In addition, OAB may also occur due to xerostomia, because it causes excessive drinking of water. If xerostomia is one of the causes of OAB, treating xerostomia may be effective. This study aimed to investigate the prevalence of xerostomia with or without overactive bladder symptoms. A web‐based questionnaire was administered to investigate the prevalence of xerostomia with or without overactive bladder symptoms. The survey included questions concerning age, gender, medical history, medications, OAB symptoms by the Overactive Bladder Symptom Score (OABSS), and xerostomia by the Dry Mouth Scale (DMS). From the analysis, a total of 21 (13.0%) participants were identified as having OAB. The prevalence of xerostomia was six (28.6%) in the OAB group and 14 (10.0%) in the non‐OAB group. OABSS and DMS were significantly higher in the OAB group than in the non‐OAB group. Urgency score and urgency incontinence score of OABSS were substantially higher in xerostomia participants than non‐xerostomia participants. The adjusted odds ratio of OAB showed DMS total score, xerostomia symptoms, accompanying symptoms, and other symptoms that were all significantly associated with OAB. These results suggested that OAB subjects, even untreated subjects, had xerostomia. It may be beneficial for clinicians to perform dry mouth management in parallel with careful choice pharmacotherapy for the wellness of OAB patients.